dampak, pembatalan, haji, pandem Dampak pembatalan Keberangkatan Haji Pada Masa Pandemi Di Kemenag Kota Bengkulu: A. Dampak 1. Pengertian dampak B. Pembatalan 1. Pengertian Pembatalan 2. Faktor-faktor Pembatalan C. Ibadah Haji 1. Pengertian Ibadah Haji 2. Rukun Haji 3. Wajib Haji 4. Syarat Haji 5. sunah-sunah Haji 6. Macam-macam Pelaksanaan Ibadah Haji 7. Hukum Mengerjakan Ibadah Haji D. Pandemi 1. Pengertian Pandemi - annisa annisa fajriani; Miti Yarmunida; Idwal B (Universitas Muhammadiyah Bengkulu, 2023)
Hajj is the fifth pillar of Islam that must be done for every Muslim, both men and women who are able and have met the requirements. Hajj is visiting the Baitullah (Ka`bah) in Mecca to perform certain acts of worship with certain conditions. The purpose of the study was to determine the impact of cancellation of Hajj Departures during the pandemic at the Ministry of Religion of Bengkulu City. Using qualitative methods, which are inquiry strategies that focus on finding meaning, understanding concepts, characteristics, symptoms, symbols, descriptions of a phenomenon that is natural and holistic, prioritizing quality and presenting in a holistic manner. Narrative of data collection techniques is done by interview, observation, and documentation. The impact of the cancellation of the Hajj departure is the longer the waiting period for the Hajj pilgrims to carry out the Hajj pilgrimage, besides that the Hajj pilgrims are worried about their health because they are getting older and their health is declining which burdens many minds.